COMPARISON OF THE EFFECTIVENESS OF OXYTOCIN MASSAGE WITH WOOLWICH MASSAGE ON BREAST MILK EXPRESSION IN POSTPARTUM MOTHERS AT THE MEISYA MEDIKA CLINIC IN 2023 - Kusuma, Khusnul Bella; Putri, Dian Priharja (HEARTY, 2025)
Background: The basic capital to form a quality human being starts in the womb accompanied by breastfeeding from an early age, especially exclusive breastfeeding. Efforts that can be made to stimulate the hormones prolactin and oxytocin in the mother after giving birth are to cause a feeling of relaxation in the mother by massaging to stimulate the nerve cells in the breasts. Research objective: to determine the comparison of the effectiveness of oxytocin massage with Woolwich massage on breast milk production in postpartum mothers at the Meisya Medika Clinic. Research method: The research design uses a non-equivalent control group design, that is, the research subjects are not randomly selected to be involved in the experimental group and the control group and both receive a pre-test and post-test group. The population in this study were all postpartum mothers who gave birth at the Meisya Medika Clinic in 2023 with a sample size of 106 people, 53 people in each group. The sampling technique is non probability sampling with purposive sampling type. The instruments for collecting data are observation sheets, and hypothesis testing using the Mann – Whitney Test because it is not normally distributed to find out whether the hypothesis is accepted or rejected. Research results and conclusions: There is a comparison of the effectiveness of oxytocin massage with Woolwich massage on breast milk production in postpartum mothers at the Meisya Medika Clinic in 2023 with a calculated z value of 42,504 and p value = 0.012. Suggestions for postpartum mothers are that they can use oxytocin massage or Woolwich massage to increase breast milk production and future researchers can develop research with other non-pharmacological therapies such as giving papaya fruit, soy milk, katuk leaves to increase breast milk production.